DEVELOPING A SYSTEM OF NATIONAL SPIRITUAL VALUES IN THE TRAINING OF FUTURE SPECIALISTS - Fuzailova Gavxar Siddikovna (Galaxy International Interdisciplinary Research Journal, 2021)
The social environment plays an in the development and improvement of society. The conditions must be created for people to work fully. The radical reforms being carried out in the Republic today are aimed at the development of society, and special attention is paid to the role and value of every citizen in society. In each of his speeches, the First President of the Republic of Uzbekistan IA Karimov focused on the human factor. In particular, he repeatedly stated in his speeches that each of us is responsible for the education of young people. Therefore, it is necessary to take a unique approach to the preparation of primary school teachers for the educational process.